Kenya Cimate-Smart Agriculture Monitoring and Evaluation Framework. - Ministry of Agriculture, Livestock, Fisheries and Cooperatives, Kenya (2021)
This monitoring and evaluation framework (M&EF) for Climate-Smart Agriculture (CSA) has been developed to foster the effective transformation of the agricultural sector toward resilient, low-carbon development, and to check whether the implementation of the Kenya Climate Smart Implementation Framework (KCSAIF) objectives, outcomes, and outputs are proceeding as planned, in order to support optimal planning and efficiency in the utilization of resources.